Skin Irritation during Video-EEG Monitoring. (2nd July 2016) - Drees, Cornelia; Makic, Mary Beth; Case, Kristen; Mancuso, Mary P.; Hill, Annette; Walczak, Pawel; Limon, Shelly; Biesecker, Kristal; Frey, Lauren
ABSTRACT: Objectives. Video-EEG (VEEG) monitoring, indicated to characterize and diagnose seizures, is recorded over several days with electrodes glued to the patient's scalp. Our investigation was designed to determine the incidence of electrode-related skin irritation during VEEG in the epilepsy monitoring unit (EMU) and implement a series of interventions to reduce the incidence of moderate to severe irritation. Methods. Between May 2012 and March 2015, EMU patients were assessed for skin lesions before electrode placement and at discharge. Prospectively gathered demographic data included: age, gender, race/ethnicity, length of monitoring (LOM), skin prep medium (SPM) used, self-reported skin sensitivity, history of skin diseases, and skin products used on the day of admission. When present, electrode-related skin irritation was graded as mild, moderate, or severe. Data were collected before any intervention (baseline-group) and thereafter with each intervention: standardization (single SPM, raising awareness, monitoring for electrode-related discomfort); face washing; applying skin barrier; replacing tape with gauze; and using disposable electrodes. Results. Data from 861 patients were analyzed (104-146 per group). At baseline, any skin irritation occurred in 27.3% of patients; it was moderate or severe in 19.1%. LOM ≥4 days and electrode position on facial skin were associated with significantly higher risk. All interventions reduced rates of skin irritation, but only the standardization intervention was statistically significant. Conclusions. During VEEG admissions, electrode-related skin irritation occurred in about one-third of patients; it was moderate to severe in one-fifth. A standardized care process with regular monitoring for discomfort led to significant improvement in the rate of irritation.